2012
DOI: 10.2174/187152812803589967
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Toll-Like Receptor 7 Stimulation in Asthma

Abstract: Asthma is an inflammatory disorder of the airways frequently characterized by an excessive Th2 adaptive immune response. Activation of Toll-like receptor (TLR)-7, a single-stranded viral RNA receptor that is highly expressed in the airways, triggers a rapid innate immune response and favors a subsequent Th1 response. Because of this role in pulmonary immunoregulation, TLR7 has gained considerable interest as a therapeutic target in asthma. Synthetic TLR7 ligands, including the imidazoquinolines imiquimod (R837… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 73 publications
1
36
1
Order By: Relevance
“…Toll‐like receptor 7 (natural ligand viral ssRNA) is of particular relevance for respiratory allergies . TLR7 polymorphism has been strongly linked with susceptibility to asthma and other atopic disorders .…”
Section: Introductionmentioning
confidence: 99%
“…Toll‐like receptor 7 (natural ligand viral ssRNA) is of particular relevance for respiratory allergies . TLR7 polymorphism has been strongly linked with susceptibility to asthma and other atopic disorders .…”
Section: Introductionmentioning
confidence: 99%
“…This result contrasts previous reports implicating IMQ as a Th1-type adjuvant 19 and as a therapeutic for mitigating Th2-driven allergy and asthma in the airways. 96 The Th2-biased antibody response in the study may reflect incomplete or insufficient IgG class switching due to the lack of a booster vaccination and/or the time point at which antibody titers were measured. Indeed, using a nanoparticle-based vaccine loaded with IMQ, a shift in IgG1/IgG2a ratio to less than unity was previously reported following three IN vaccinations over 28 weeks.…”
Section: Resultsmentioning
confidence: 97%
“…Adoptive transfer of TLR competent pDCs was shown to block these exaggerated inflammatory responses and increase IFN-γ release [94]. Studies using synthetic TLR7 ligands (R837 and R848) have shown that activation of the receptor prevented airway hyper-responsiveness, eosinophilic infiltration and goblet cell hyperplasia in an ovalbumin model of asthma [95]. There were also decreased levels of IL-5 and LTB4 in bronchoalveolar lavage fluid, suggesting that TLR7 dampens allergic airway responses [36].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%